A Book Of Computer Science for Human Resource Development Centers Pakistan Army - Collage Of Army Education Upper Topa Muree (GHQ Rawalpindi Army Education Publishing House, 2007)
This title provides broad coverage and clear explanations of the entire computer science discipline. It features extended ethical sections in software engineering and database systems, in addition to optional sections at the end of each chapter.
Include Glossary, Illustrations and Tables
Keywords: Computer science -- Electronic data processing -- Electronic digital computers